2020
DOI: 10.3354/dao03502
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Batrachochytrium dendrobatidis in Sweden: higher infection prevalence in southern species

Abstract: The chytrid fungus Batrachochytrium dendrobatidis (Bd) has caused worldwide declines in amphibian populations. While Bd is widespread in southern and central Europe, its occurrence and distribution in northernmost Europe is mostly unknown. We surveyed for Bd in breeding anurans in Sweden by sampling 1917 amphibians from 101 localities and 3 regions in Sweden (southern, northern and central). We found that Bd was widespread in southern and central Sweden, occurring in all 9 investigated species and in 45.5% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…Since Ra has higher infection prevalence in in the wild (Meurling et al 2020) and higher infection tolerance (this study), we suggest that Ra may act as a reservoir species and a possible vector for Bd-transmission to more sensitive species such as Bb. Indeed, Kärvemo et al (2019) showed that Bb populations coexisting with Ra had higher Bd-prevalence than populations breeding in ponds without Ra.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Since Ra has higher infection prevalence in in the wild (Meurling et al 2020) and higher infection tolerance (this study), we suggest that Ra may act as a reservoir species and a possible vector for Bd-transmission to more sensitive species such as Bb. Indeed, Kärvemo et al (2019) showed that Bb populations coexisting with Ra had higher Bd-prevalence than populations breeding in ponds without Ra.…”
Section: Discussionmentioning
confidence: 63%
“…Bd is widespread in the southern parts of Sweden (Kärvemo et al 2018, 2019, Meurling et al 2020). However, in a pattern similar to much of Europe (Lips 2016, Scheele et al 2019, no cases of chytridiomycosis or unusual die-offs have been found in Sweden.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fish are reported to have negative impacts on the growth and prevalence of amphibian populations (Pope, 2008;Semlitsch et al, 2015;Shulse et al, 2012) as well as their behaviour (Winandy et al, 2015). Amphibian population declines are also related to habitat loss or deterioration, over-exploitation, climate change and diseases (Cohen et al, 2019;Meurling et al, 2020;Stuart et al, 2004) and therefore are of conservation interest when creating new aquatic habitats. Negative effects of fish on amphibians, especially focusing on prey-predator occurrences, are well documented in natural wetlands (Hartel et al, 2007) and created ponds (Semlitsch, 1987).…”
Section: Introductionmentioning
confidence: 99%